2018
DOI: 10.12659/msm.908302
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of T-Helper 9 Activation in a Mouse Model of Allergic Rhinitis

Abstract: BackgroundWe aimed to investigate the role of T-Helper (TH) 9 cells in the pathogenesis of allergic rhinitis (AR) in mice.Material/MethodsAn AR model was produced in BALB/c mice, and the viral encoding interleukin (IL)-9 silencing sequence was used to reduce IL-9 expression. The experiment was divided into a control group, an AR group, an IL-9 shRNA+AR group, and a vector+AR group. Hematoxylin and eosin (H&E) staining was used to detect pathological changes. The cytokine expression was detected by ELISA method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Collectively, as shown in Figure 1, various cytokines are involved in the differentiation of IL‐9+CD4+ T cells as well as IL‐9 secretion. Although the role of IL‐9+CD4+ T cells and its prominent cytokine, IL‐9, has been clarified in the autoimmune diseases, 11 allergic diseases 12,13 and tumours, 14 limited studies have investigated its role in the infectious diseases. Leishmaniasis, as an infectious disease, is caused by obligatory intracellular protozoan parasite belonging to the genus Leishmania (L) .…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, as shown in Figure 1, various cytokines are involved in the differentiation of IL‐9+CD4+ T cells as well as IL‐9 secretion. Although the role of IL‐9+CD4+ T cells and its prominent cytokine, IL‐9, has been clarified in the autoimmune diseases, 11 allergic diseases 12,13 and tumours, 14 limited studies have investigated its role in the infectious diseases. Leishmaniasis, as an infectious disease, is caused by obligatory intracellular protozoan parasite belonging to the genus Leishmania (L) .…”
Section: Introductionmentioning
confidence: 99%
“…Such as Schwartz et al (2019) found that the vitamin A metabolite, retinoic acid, could inhibit Th9 differentiation, which was associated with human allergic inflammation. Therefore, immunotherapy against Th9 cells and its functional factor IL-9 may be one of the new treatment strategies for allergic inflammatory diseases (Dugas et al , 1993; Hoppenot et al , 2015; Reuter et al , 2016; Gu et al , Cao and 2017; Koch et al , 2017; Jiang et al , 2018).…”
Section: Th9 Cells and Clinical Diseasesmentioning
confidence: 99%
“…Many inflammatory and autoimmune diseases are impacted by the cytokine network, with IL‐9 being a crucial component 9–11 . There has been a rise in many studies indicating that IL‐9 can be both a negative and positive regulator of tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…8 Many inflammatory and autoimmune diseases are impacted by the cytokine network, with IL-9 being a crucial component. [9][10][11] There has been a rise in many studies indicating that IL-9 can be both a negative and positive regulator of tumorigenesis. It exerts different immunoregulatory functions in different tumor microenvironments (including melanoma, small-cell lung cancer, hepatocellular carcinoma, colorectal cancer, etc.).…”
Section: Introductionmentioning
confidence: 99%